Calculation of Strength of Fiber Reinforced Concrete Beams Using Abaqus Software - Razzakov Sobirjon Jurayevich; Martazayev Abdurasul Shukirillayevich (Peerian Journals Publishing, 2022)
In the research work, the strength, stress-strain state, crack-resistance of fiber reinforced concrete beams dispersed with reinforced concrete and basalt fibers were analyzed using ABAQUS software. It was found that the strength and toughness of fiber reinforced concrete beams increased compared to ordinary reinforced concrete beams.
Keywords: reinforced concrete; beam; stress; strain